Redressing Fundamental Rights Violations by the EU (Cambridge University Press, 2025)
This volume is for academics working on the rule of law, fundamental rights, and judicial or administrative remedies for redress, as well as policy makers working on accountability of EU public power, and civil society organisations with a vision to stimulate change through strategic litigation. Also available as Open Access on Cambridge Core.